Postoperative Incisional Bleeding Due To Amyloidosis: A Case Report - Beksaç, Sinan; Özlü, Tülay; Katlan, Doruk (Gynecology Obstetrics & Reproductive Medicine, 2006)
Here, we represent a case of a 36 years old woman who had massive bleeding from the site of cesarean incision on the same day with the surgery. She was known to have Familial Mediterranean Fever (FMF) f or 22 years and a renal biopsy perf ormed 10 years ago confirmed a diagnosis of renal amyloidosis.